2007
DOI: 10.1093/carcin/bgm018
|View full text |Cite
|
Sign up to set email alerts
|

The t10,c12 isomer of conjugated linoleic acid stimulates mammary tumorigenesis in transgenic mice over-expressing erbB2 in the mammary epithelium

Abstract: Conjugated linoleic acid (CLA), a family of isomers of octadecadienoic acid, inhibits rat mammary carcinogenesis, angiogenesis, and lung metastasis from a transplantable mammary tumor. c9,t11-CLA, the predominant isomer in dairy products, and t10,c12-CLA, a component of CLA supplements, are equally effective. The objective of the current studies was to test the efficacy of these two CLA isomers in a clinically relevant breast cancer model. Transgenic mice over-expressing erbB2 in the mammary epithelium were fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 40 publications
(48 reference statements)
9
50
3
1
Order By: Relevance
“…Since dietary CLA is incorporated into mammary adipocyte triglycerides, it may be possible to achieve an effective local concentration of c9,t11-CLA in the in vivo setting. This is an important consideration, given the potentially serious side effects of t10,c12-CLA seen in some, although not all studies, including our recent observation that t10,c12-CLA stimulates mammary tumorigenesis and metastasis in mice which overexpress erbB2 in the mammary epithelium ( [33] and references within). Work is continuing in our laboratory on the mechanism by which the individual CLA isomers exert their effects, with the goal of defining an optimal CLA strategy for chemoprevention.…”
Section: Discussionmentioning
confidence: 99%
“…Since dietary CLA is incorporated into mammary adipocyte triglycerides, it may be possible to achieve an effective local concentration of c9,t11-CLA in the in vivo setting. This is an important consideration, given the potentially serious side effects of t10,c12-CLA seen in some, although not all studies, including our recent observation that t10,c12-CLA stimulates mammary tumorigenesis and metastasis in mice which overexpress erbB2 in the mammary epithelium ( [33] and references within). Work is continuing in our laboratory on the mechanism by which the individual CLA isomers exert their effects, with the goal of defining an optimal CLA strategy for chemoprevention.…”
Section: Discussionmentioning
confidence: 99%
“…At sacrifice, mammary glands and tumors were removed and prepared for whole mount analysis and/or fixed in formalin. Lungs of the euthanized mice were perfused with India ink through the trachea, removed, and fixed as described previously (20).…”
Section: Mammary Tumorigenesis Studymentioning
confidence: 99%
“…Whole mounts of the mammary glands were prepared as described previously (20). Using photographic images of the whole mounts, with verification under the 4× objective of the microscope, the number of hyperplasias/lesions in mammary glands 1 to 5 on one side of each mouse was counted in three groups according to size (0.2-0.5, 0.5-1.0, and >1.0 mm in diameter).…”
Section: Mammary Tumorigenesis Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Part of the effects of CLA are isomer-specific and some studies showed adverse effects of t10,c12-CLA (Bhattacharya et al, 2006;Ip et al, 2007). Similarly, total trans fatty acids (FA), including monoenoic, can alter cardiovascular risk markers; however, the specificity of individual isomers remains an area of controversy, where some suggest a similar effect of all trans FA (Brouwer et al, 2010), whereas others assume natural trans FA, mainly of milk origin, are less deleterious as compared with industrial trans FA (Tardy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%